God's Love Language is Obedience: Structure and Substance of 1 John 5:1-5 - Paulus Dimas Prabowo; Sanghee Kim; John Marlin (Sekolah Tinggi Teologi Injili Indonesia (STTII) Yogyakarta, 2025)
This study aims to present the structure and substance of 1 John 5:1-5, in light of various interpretations and even disagreements over whether 1 John 5:1-5 constitutes a single structural unit. The main issue discussed in this study is: what is the structure and what is the substance of 1 John 5:1-5? Within the post-positivist paradigm and the evangelical theological perspective, the author will employ a stylistic analysis to examine chiasmus and repetition in 1 John 5:1-5. The study's results affirm strong evidence that 1 John 5:1-5 forms a single structural unit, and its substance is 'obedience as the language of love toward God.' Although borrowing the language popularized by Gary Chapman regarding the language of love, this study does not employ his theory. Future research could delve into systematic theological aspects such as the concept of being born again, or integrate it with social factors in terms ofrelated to love for others.